High-risk prostate cancer: factors predicting biochemical recurrence after radical prostatectomy - Ulys, Albertas; Ulytė, Agnė; Dziameshka, Pavel; Sukonko, Oleg; Krasny, Sergei; Polyakov, Sergei; Smailytė, Giedrė (Acta medica Lituanica, 2015)
Background/objective. Predictive criteria are needed to evaluate the risk of disease progression after radical prostatectomy. Such criteria would help to select patients most likely to benefit from adjuvant or multimodality treatment. Our aim was to identify predictive factors for biochemical recurrence among the  pre- and post-operative parameters in high-risk prostate cancer patients after radical prostatectomy. Methods. Data on high-risk prostate cancer patients between 2005 and 2009 were retrospectively reviewed in two cancer centers: National Cancer Institute, Vilnius, Lithuania, and N.  N.  Alexandrov National Cancer Centre of Belarus, Minsk, Belarus. 199 patients were selected for the  study. The  pre-operative independent variables were T stage, pretreatment PSA level and Gleason score. Surgical margins and perineural invasion were additionally known for 122 patients. The outcomes measured were biochemical recurrence free and overall survival. The mean follow-up time was 5.8 years. Results. Lower T stage (p = 0.001) and pretreatment PSA (p = 0.0001) were associated with better survival. In the multivariate analysis of pre-operative factors, high T stage (p = 0.008) and pretreatment PSA (p = 0.009) were predictive of biochemical recurrence. When postoperative parameters were included in the multivariate analysis, only pretreatment PSA (p = 0.01), positive surgical margins (p = 0.003) and perineural invasion (p = 0.03) remained relevant independent predictors of biochemical recurrence. Conclusions. Pretreatment PSA, positive surgical margins and perineural invasion were independent predictors of biochemical recurrence after radical prostatectomy in high-risk prostate cancer patients, while the  T stage became insignificant after adjusting for postoperative parameters.
Keywords: high-risk prostate cancer; radical prostatectomy; biochemical recurrence